Children's social status and anticipated shame and guilt experiences. (June 2019) - Stapleton, Charles Matthew; Zhang, Hui; Kitzmann, Katherine M.; Cohen, Robert
Previous research indicates that the behavioral profile of high-status children is not monolithic but varied. This study contributes to the existing research on high-status children by showing that they are also an emotionally diverse group in terms of their anticipated shame and guilt experiences. Children ( N = 163, aged 8–12 years) nominated classmates who were perceived as popular, socially preferred, respected, and overtly aggressive. Regarding anticipated shame and guilt experiences, children also related how much they would experience shame and guilt and display correlated behaviors after reading stories which varied the transgression type (intentional harm, unintentional harm, and incompetent behavior) and the transgression frequency (many times vs. once). We found that children who were perceived by other children to be both highly popular and high in another area of social status related to a communal goal orientation (social preference, respect, and nonaggression) anticipated significantly more shame and guilt feelings than children who were perceived to be only highly popular and children who were low in social status. Moreover, these children also anticipated using significantly more appeasement than apologetic strategies when they imagined acting incompetently many times; a pattern not in evidence with other children. These findings suggest that children who are viewed as both popular and communal are more sensitive to the ways transgressions could influence what they would feel and what they would do, compared to children who are viewed as popular but not communal and children who are neither popular nor communal.